Les « valeurs de santé » de l’hôpital Beaujon à Clichy (Hauts-de-Seine) entre 1935 et 2023 - Lila Bonneau (In Situ)
This article examines the principles of hygiene that were integrated into the design of the Beaujon hospital, opened in 1935 at Clichy in what is today the Hauts-de-Seine department, bordering Paris. The hospital was built for the city’s public health authority (Assistance Publique) by a team of architects including Jean Walter, Urbain Cassan and Louis Plousey. The principles involved were aimed at combatting the main sanitary afflictions of the day, tuberculosis, cancer, syphilis and alcoholism. They were also concerned by the damage resulting from the First World War, at a time when society understood that an unhealthy environment or inappropriate hygiene, along with poor sanitary habits, could contribute to the development of illnesses. The healthcare establishment, was designed to offer the sick the best possible conditions for recovery.The article looks at the architectural arrangements used during the interwar period and designed to improve conditions of hygiene for users – staff included – in this building which was the first multi-storey hospital in France. These arrangements have been much altered since the hospital was built, but today form what we call the site’s ‘health values’.The article addresses the present-day issues of the building’s urban and landscape heritage status, with regards to the original design and considering the future of the hospital, due to be closed in 2030.